Relationship between Knowledge and Attitudes of Students with Covid-19 Prevention Measures in the study program of 3rd Diploma of Nursing, Faculty of Medicine, Mulawarman University - Ruminem, Ruminem; Sari, Rita Puspa; Nopriyanto, Dwi; Aminuddin, Muhammad; Nur, Syukma Rahmadhani Faizal (Jurnal Kesehatan Pasak Bumi Kalimantan, 2021)
COVID-19 or Coronavirus Disease 2019 is a new disease that can cause respiratory problems and pneumonia caused by infection with Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Efforts to prevent the transmission of the Covid-19 disease are very important, considering that the corona virus is easily transmitted from human to human through coughing/sneezing (droplets) and contact with sufferers. Preventive measures against COVID-19 such as washing hands, wearing masks and social distancing carried out by students can be influenced by knowledge about COVID-19 and attitudes towards preventing Covid-19. The purpose of this study was to determine the relationship between Knowledge and Attitudes of Students with Covid-19 Prevention Measures in the study program of 3rd Diploma of Nursing, Faculty of Medicine, Mulawarman University Research  Method: The research design is cross sectional, and the research sample is students of 3rd diploma of Nursing Study Program, Faculty of Medicine Mulawarman University, the sampling technique is a total sampling of 176 students. The research instrument is a questionnaire. Data analysis was univariate and bivariate with Chi Square test.The results of the study: The knowledge of respondents about Covid-19 was in a good category (56.5%), the attitude of the respondents was more positive (65.6%) and the majority of respondents' actions in preventing Covid-19 were in a good category (52.8%). There is a relationship between knowledge and preventive measures for Covid-19 (p.value 0.040 < 0.05), There is no relationship between student attitudes and preventive measures for Covid-19 (p.value 0.845 > 0.05).Conclusion: There is a relationship between knowledge and covid-19 prevention measures, the attitude is not related to action. There is a need for education to increase knowledge and positive attitudes in supporting COVID-19 prevention measures. Keywords: Covid-19, Knowledge, Action, attitude, students